Pengungkapan semula politik Islam melalui pendekatan Islam Hadhari - Mahmood Zuhdi Haji Abdul Majid, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
The failure of Muslim community to portray Islam as progressive system of life gives impression that Islam fails to address the challenges facing the modern world’s development of today. This total failure of bringing development to Muslim communities and Muslim states traps them forever. Several approaches have been tried and implemented to bring back the glory of Muslim communities, but the result has yet to be observed. As the result, Muslim communities are facing with the mix issues of truth (haq) and fault (kebatilan). This paper explores brief overview of several approaches implemented by Muslim communities to bring back the glory of Islamic civilisation. The writer proposes that the approach of Islam Hadhari or Islamic civilisational approach be implemented; focusing on human and Muslim community developments, as the best approach in the effort to bring back the glory of human civilisation.